Endoplasmic Reticulum Stress, Unfolded Protein Response, and Cancer Cell Fate - Corazzari, Marco; Gagliardi, Mara; Fimia, Gian Maria; Piacentini, Mauro (Frontiers in Oncology, 2017)
Perturbation of endoplasmic reticulum (ER) homeostasis results in a stress condition termed “ER stress” determining the activation of a finely regulated program defined as unfolded protein response (UPR) and whose primary aim is to restore this organelle’s physiological activity. Several physiological and pathological stimuli deregulate normal ER activity causing UPR activation, such as hypoxia, glucose shortage, genome instability, and cytotoxic compounds administration. Some of these stimuli are frequently observed during uncontrolled proliferation of transformed cells, resulting in tumor core formation and stage progression. Therefore, it is not surprising that ER stress is usually induced during solid tumor development and stage progression, becoming an hallmark of such malignancies. Several UPR components are in fact deregulated in different tumor types, and accumulating data indicate their active involvement in tumor development/progression. However, although the UPR program is primarily a pro-survival process, sustained and/or prolonged stress may result in cell death induction. Therefore, understanding the mechanism(s) regulating the cell survival/death decision under ER stress condition may be crucial in order to specifically target tumor cells and possibly circumvent or overcome tumor resistance to therapies. In this review, we discuss the role played by the UPR program in tumor initiation, progression and resistance to therapy, highlighting the recent advances that have improved our understanding of the molecular mechanisms that regulate the survival/death switch.